2011
DOI: 10.3109/10837450.2011.620970
|View full text |Cite
|
Sign up to set email alerts
|

Dose emission and aerodynamic characterization of the terbutaline sulphate dose emitted from a Turbuhaler at low inhalation flow

Abstract: Previously, dose emission below 30 L min(-1) through DPI has not been routinely determined. However, during routine use some patients do not achieve 30 L min(-1) inhalation flows. Hence, the aim of the present study was to determine dose emission characteristics for low inhalation flows from terbutaline sulphate Turbuhaler. Total emitted dose (TED), fine particle dose (FPD) and mass median aerodynamic diameter (MMAD) of terbutaline sulphate Turbuhaler were determined using inhalation flows of 10-60 L min(-1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…At inhalation flow rate of 10, 20, 30, 40, 50 and 60 L min À1 the mean (SD) FPD were 1.6 (0.8), 1.9 (0.7), 5.9 (2.5), 12.8 (4.3), 24.2 (1.9) and 36.5 (5.1) % of the 500 mg terbutaline sulphate nominal dose, respectively. 24 This study showed that the terbutaline sulphate from Turbuhaler has a flow dependent dose emission property and flow dependent fine particle dose characteristic. The TED and FPD were significantly increased with the increase of the flow (p < 0.001).…”
Section: Discussionmentioning
confidence: 82%
“…At inhalation flow rate of 10, 20, 30, 40, 50 and 60 L min À1 the mean (SD) FPD were 1.6 (0.8), 1.9 (0.7), 5.9 (2.5), 12.8 (4.3), 24.2 (1.9) and 36.5 (5.1) % of the 500 mg terbutaline sulphate nominal dose, respectively. 24 This study showed that the terbutaline sulphate from Turbuhaler has a flow dependent dose emission property and flow dependent fine particle dose characteristic. The TED and FPD were significantly increased with the increase of the flow (p < 0.001).…”
Section: Discussionmentioning
confidence: 82%
“…9 Only 7–46% of Turbuhaler (TH) users 10 and 13–50% of Accuhaler (ACC [Diskus] users) 10 are found to have correct technique, and incorrect technique is associated with worse asthma outcomes. 11 Training to improve the inhaler technique should thus be an important component of asthma education.…”
Section: Introductionmentioning
confidence: 99%
“…57 Failure to do so results in partial delivery of the medication to the lungs 29 and increased drug deposition in the mouth and pharynx. 57,60,62,63 Maintaining a forceful and deep inhalation from the start of the inhalation maneuver and for as long as possible ensures that most patients can use a powder inhaler (Turbuhaler and Diskus) irrespective of the resistance of the device or their disease severity. 64 However, although most patients can achieve the required flow, 65,66 flow is more likely to be a problem for the Turbuhaler than for the lower resistance Diskus.…”
Section: Evidence For Inclusion Of Individual Technique Steps In Devimentioning
confidence: 99%